Analysis of the Relationship Between Reading Literacy and Numeracy Skills with Science Learning Outcomes of Students based UKN and ANBK - Anjelia, Bella (CV. ITTC INDONESIA, 2025)
The study investigates the relationship between reading literacy, numeracy, and science learning outcomes among ninth-grade students at Pondok Pesantren Salafiyah Mutiara Sunnah Palembang. It aims to address persistent challenges in literacy and numeracy within Islamic boarding schools, emphasizing their impact on academic performance. Employing a quantitative approach with a correlational method, data were collected from 28 students using literacy and numeracy tests alongside science scores from national assessments. Results reveal a strong positive correlation between reading literacy and science outcomes (r = 0.701, p < 0.01), underscoring the critical role of reading skills in comprehending scientific concepts. Numeracy showed a weaker, non-significant relationship (r = 0.336, p = 0.080) with science outcomes but was strongly correlated with literacy (r = 0.601, p < 0.05). These findings highlight the interconnectedness of literacy and numeracy as foundational competencies for science education. The study recommends integrative educational strategies that combine traditional methods with modern technologies to enhance these skills, ultimately improving students' academic success and preparedness for 21st-century challenges.